2016
DOI: 10.1111/inr.12239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intimate partner violence on health of women of Palestinian origin

Abstract: Social desirability and use of convenience sampling are major limitations of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
0
24
1
Order By: Relevance
“…), resiliency, and coping strategies. Although there was no gender difference in depressive symptom severity in this study, there was evidence in the literature of gender‐specific vulnerabilities in refugee populations, particularly among women in regard to psychological health, discrimination, safety, exploitation, violence, and harassment (Al‐Modallal, , ). Socioecological factors, such as income, employment, and education, also have been shown to be robust predictors of physical and psychological health (Marmot et al., ).…”
Section: Discussion and Recommendationscontrasting
confidence: 52%
See 1 more Smart Citation
“…), resiliency, and coping strategies. Although there was no gender difference in depressive symptom severity in this study, there was evidence in the literature of gender‐specific vulnerabilities in refugee populations, particularly among women in regard to psychological health, discrimination, safety, exploitation, violence, and harassment (Al‐Modallal, , ). Socioecological factors, such as income, employment, and education, also have been shown to be robust predictors of physical and psychological health (Marmot et al., ).…”
Section: Discussion and Recommendationscontrasting
confidence: 52%
“…Forced displacement is traumatic and often an unwanted social change that can lead to a loss of identity and physical, psychological, and socioeconomic livelihood (Lori & Boyle, ; Marie, Hannigan, & Jones, ; UNHCR, ). For many refugee women, intimate partner and gender‐based violence and associated mental health conditions have been identified as additional issues (Al‐Modallal, , ). The poor physical health, living, and socioeconomic conditions of Palestinian refugees in Jordan have been documented (Tiltnes & Zhang, ), although current literature about their psychological health could not be found.…”
mentioning
confidence: 99%
“…For most outcomes, there was a mixture of significant and non-significant results. Six studies looking at pain all found significant associations; Al-Modallal found associations for some types of violence but not others [30]. Meta-analysis produced a pooled OR of 2·6 (95% CI 1·6–4·1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies had non-representative populations e.g. large proportion of military police husbands [42], high level of female employment [40], or only refugee participants [27, 28, 30, 34, 35, 52, 53, 55]. Twenty-nine papers reported response rates (which were generally high) but few assessed for non-response bias.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Such violence is associated with different factors including but not limited to low socioeconomic status, presence of conflict, low levels of education, alcohol and/or drug use, having multiple partners, and life stressors. [3567] Women who exposed to IPV reported high level of anxiety and depression,[8] in addition to negative delivery consequences when victims are pregnant. [9] Many cases require healthcare interventions and some are prevented from seeking health care.…”
Section: Introductionmentioning
confidence: 99%